Sacred schisms: how religions divide - Lewis, James R.; Lewis, Sarah M. (Cambridge Univ. Press, 2009)
Introduction / James R. Lewis and Sarah Lewis -- Part I: Theoretical overview -- Understanding schisms : theoretical explanations for their origins / Roger Finke and Christopher P. Scheitle -- Part II: Survey of schisms in selected traditions -- Charismatic authority in Islam : an analysis of the cause of schisms in the ummah / Ron Geaves -- Schisms in Buddhism / Alan Cole -- Schisms in Japanese new religious movements / Robert Kisala -- Part III: Christian traditions -- Finishing the mystery : the watch tower and 'the 1917 schism' / George D. Chryssides -- Challenges to charismatic authority in the unificationist movement / David G. Bromley and Rachel S. Bobbitt -- Persecution and schismogenesis : how a penitential crisis over mass apostasy facilitated the triumph of Catholic Christianity in the Roman Empire / Joseph M. Bryant -- Part IV: Western esoteric traditions -- Church universal and triumphant : shelter, succession and schism / Susan J. Palmer and Michael Abravanel -- Schism and consolidation : the case of the theosophical movement / Olav Hammer -- Satanists and nuts : the role of schisms in modern satanism / Jesper Aagaard Petersen -- Schism as midwife : how conflict aided the birth of a contemporary pagan community / Murphy Pizza -- Part V: Non-western/postcolonial traditions -- Succession, religious switching, and schism in the Hare Krishna Movement / E. Burke Rochford, Jr. -- Schisms within Hindu guru groups : the Transcendental Meditation movement in North America / Cynthia Ann Humes -- Schism in Babylon : colonialism, Afro-Christianity, and Rastafari / Christopher Partridge